Shadowlands : memory and history in post-Soviet Estonia - Wulf, Meike, 1970- 1970- (Berghahn, 2016)
"Located within the forgotten half of Europe, historically trapped between Germany and Russia, Estonia has been profoundly shaped by the violent conflicts and shifting political fortunes of the last century. This innovative study traces the tangled interaction of Estonian historical memory and national identity in a sweeping analysis extending from the Great War to the present day. At its heart is the enduring anguish of World War Two and the subsequent half-century of Soviet rule. Shadowlands tells this story by foregrounding the experiences of the country's intellectuals, who were instrumental in sustaining Estonian historical memory, but who until fairly recently could not openly grapple with their nation's complex, difficult past"...From publisher's website